Feasibility Study of Digital Administration and Digital Marketing of SMEs Products at The Investment Gallery of Manado State Polytechnic - Paendong, Melky; Kumaat, Arief Perdana; Kolondam, Arifmanuel; Maramis, Diana (Universitas Diponegoro, 2023)
The challenges for SMEs in Indonesia are growing, especially in terms of competing in an increasingly competitive and dynamic market. One of the efforts that SMEs can undertake to enhance their competitiveness is by leveraging digital technology in managing their businesses, from administrative systems to digital marketing activities for SME products. Therefore, this research aims to conduct a feasibility study of digital administration and digital marketing systems for SME products, with the research location being the Investment Gallery of the State Polytechnic of Manado, which serves as a showcase and sales platform for local SMEs' flagship products, managed by the Marketing Laboratory of the Manado State Polytechnic (Polimdo).This research was conducted using a survey method involving respondents from SMEs participating in the Manado State Polytechnic (Polimdo) Investment Gallery. The collected data were analyzed using both quantitative and qualitative descriptive analysis. The observational results indicate that the majority of SMEs participating have knowledge of digital technology, but only a small portion have implemented it in their businesses.In this context, the use of digital administration and digital marketing systems can help SMEs optimize their administrative processes and enhance efficiency in managing their businesses. Additionally, the use of digital technology can assist SMEs in expanding their markets and increasing their sales. However, despite the significant benefits of using digital technology in SMEs, there are still some challenges to overcome, such as the limited technological knowledge of SME owners. Therefore, the implementation of digital administration and digital marketing systems for SMEs requires a suitable approach to ensure optimal benefits.